Investigasi Pemahaman Calon Guru tentang Konsep Kalor, Kerja, dan Proses-Proses Termodinamika - Triwiyono Triwiyono; Albert Lumbu (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
The purpose of this study are to describe the understanding of prospective teachers on the concepts of heat, work, and thermodynamic process and the difficulties they face in learning the concepts of thermodynamics. This research was conducted using qualitative method. Data were collected using a diagnostic test and interview. The subjects were students of physics education, University of Cendrawasih who had attended the lectures of thermodynamics, as many as 39 people. The results of this study indicate that student teachers do not understand the concept of heat, work, and thermodynamic process well. Students can analyze the problem and solve the majority of them (30%). The settlement issue is not based on prior knowledge that already exists. Students have difficulty distinguishing the work done by the system or the environment. Students also have difficulty understanding the process in a diagram or change it in a different diagram.